Non-catalytic roles for TET1 protein negatively regulating neuronal differentiation through srGAP3 in neuroblastoma cells. Issue 5 (25th April 2016) - Gao, Jie; Ma, Yue; Fu, Hua-Lin; Luo, Qian; Wang, Zhen; Xiao, Yu-Huan; Yang, Hao; Cui, Da-Xiang; Jin, Wei-Lin
Abstract: The methylcytosine dioxygenases TET proteins (TET1, TET2, and TET3) play important regulatory roles in neural function. In this study, we investigated the role of TET proteins in neuronal differentiation using Neuro2a cells as a model. We observed that knockdown of TET1, TET2 or TET3 promoted neuronal differentiation of Neuro2a cells, and their overexpression inhibited VPA (valproic acid)-induced neuronal differentiation, suggesting all three TET proteins negatively regulate neuronal differentiation of Neuro2a cells. Interestingly, the inducing activity of TET protein is independent of its enzymatic activity. Our previous studies have demonstrated that srGAP3 can negatively regulate neuronal differentiation of Neuro2a cells. Furthermore, we revealed that TET1 could positively regulate srGAP3 expression independent of its catalytic activity, and srGAP3 is required for TET-mediated neuronal differentiation of Neuro2a cells. The results presented here may facilitate better understanding of the role of TET proteins in neuronal differentiation, and provide a possible therapy target for neuroblastoma.